"Can't stop the boy": Philip Morris' use of Healthy Buildings International to prevent workplace smoking bans in Australia. (26th November 2003) - Chapman, S; Penman, A
Abstract : Objective: To document the relationship of the indoor air consultancy company Healthy Buildings International (HBI) with the Australian tobacco industry. Design: Systematic keyword and opportunistic website searches of tobacco industry internal documents made available through the Master Settlement Agreement. Results: Since 1987 HBI has played a high profile role in advancing the Australian tobacco industry's concerns to prevent building owners introducing smoke-free workplaces by advocating for ventilation solutions. HBI invoiced Philip Morris' US lawyers Covington and Burling for work undertaken in Australia and sought to publicly deny its association with the industry. HBI breached Standards Australia protocols in providing PM with confidential public submissions made to a review of the Australian standard on ventilation and acted as an undeclared cipher into the review for Philip Morris's concerns, leading to the eventual dismissal of the HBI representative from the standards subcommittee. Conclusions: HBI in Australia exemplifies the tobacco industry's use of third party strategy in publicly advancing a case against smoke-free indoor air.